Social networks in the life of a schoolchild: educational opportunities and risks - Sárközi Karolina; Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Social networks today play an increasingly significant role in the lives of schoolchildren, shaping not only their modes of communication but also providing an environment for learning, personal development, and self‑identity. The use of social networks can facilitate access to a variety of educational resources—video lessons, online courses, open lectures, interest-based communities— where students exchange knowledge and experience, ask questions, and participate in project work [1]. Moreover, social networks can enhance academic motivation and a sense of belonging to school: when a student uses social platforms for educational purposes and interacts with classmates or teachers, this can improve the emotional climate and help develop collaboration and communication skills [2]. During periods of distance learning or limited offline contact, social networks often become an important link in maintaining the educational process and providing social support [3]. However, there are significant risks. The first is the potential for social media addiction, which may manifest as reduced concentration, increased distractions, and decreased academic productivity. Research shows that excessive social media use is associated with mental health problems, such as anxiety, depression, and sleep disturbances [4]. The second risk is privacy violation, the danger of phishing, and manipulation through false information or content promoting unrealistic standards of appearance and social status. These factors can undermine students’ self-esteem, lead to social comparison, and cause psychological discomfort. The third aspect is that social networks can become an environment for cyberbullying, online harassment, or isolation, where virtual interactions do not support real social skills or emotional support and, on the contrary, may create feelings of loneliness or exclusion [5]. It is essential that educational institutions, parents, and students themselves work on developing media literacy, emotional intelligence, and healthy social media habits. This includes recognizing fake content, managing screen time, setting privacy boundaries, and critically evaluating information [6]. In conclusion, social networks can be a powerful tool in a student’s life if their educational potential is used consciously and if the associated risks are actively minimized through education, support, and responsible engagement in the digital environment.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: social networks; schoolchildren; education